ANALISIS KUALITAS DATA KELUARAN HARIAN ELEKTRON AKSELERATOR LINIER - Heru Santoso; Muhammad Hamdi; Saktioto Saktioto (Komunikasi Fisika Indonesia, 2020)
Linac radiotherapy measurentoften experience instability. One of the irradiation errors with Linac can occur because the radiation beam that comes out is not expected properly. Determination of the correction factor and linearity is important to analyze the charge output of the electron energy emitted by Linac's modality to see the stability of the emitted charge. This study uses Electron Linear Accelerator Electron beam daily output data with a 10 cm × 10 cm applicator, 100 cm SSD, 0.125 cc cylindrical ionization detector PTW type 31010 Semiflek and uses a slab solid phantom with energy variations of 6 MeV, 8 MeV, 10 MeV, 12 MeV and 15 MeV. The measurement results are calculated using the IAEA TRS 398 protocol. The result of linearity correction factor of 96.87% which shows the stability value of the electron beam load output is very good, and the results of the correction factor show the enumeration values of each energy 6 MeV, 8 MeV, 10 MeV, 12 MeV and 15 MeV namely 0.030342129 nC, 0.03034 nC, 0.03034 nC, 0.03034 nC and 0.03034 nC values respectively still within the tolerance range of measurement ± 1. The correction factor that has been obtained is used as a parameter in calculating the absorbance dose to the maximum depth.